(untitled) (Journal of Hama University, 2026)
The research aimed to identify the role of the Faculty of Education at Hama University in achieving cultural sustainability from the perspective of faculty members during emergencies . To achieve the research objectives, the researcher used the descriptive-analytical approach, designing a questionnaire consisting of (22) items in its final form. The questionnaire was administered to a purposive sample comprising the research community of (31) faculty members at the Faculty of Education at Hama University. The study revealed that the role of the Faculty of Education in achieving cultural sustainability during emergencies was average, and that its role in achieving human and educational development during emergencies was average. The research also found no statistically significant difference between the average scores of faculty members attributed to the variable of specialization (child education - special education), and there were statistically significant differences between the average scores of faculty members attributed to the variable of gender, in favor of males